Phenomenological Study : No Mobile Phone Phobia (Nomophobia) at Junior High School’s Students - Sri Hindriyastuti; Herlina Wietya Anggraeni; Gardha Rias Arsy; Vera Fitriana (International Journal of Medicine and Health, 2025)
Background: One form of current technological development is the smartphone. Initially, smartphones were only used by adults, but in this modern era, many teenagers use smartphones. One of the positive impacts of smartphones for school-age youth is being able to find learning materials easily and being able to communicate remotely with teachers, while the excessive use of smartphones has a negative impact, both physically and psychologically. Another bad impact is nomophobia. Nomophobia or commonly known by the abbreviation "No Mobile Phone Phobia" or the disease can not be far from a mobile phone. Nomophobia is also defined as a feeling of anxiety when kept away from a sartphone. Objective: To find out the experience of nomophobia in adolescents at SMP 1 Gebog Kudus. Method: The type of research used is qualitative research using a phenomenological approach. The selection of participants was carried out using a purposive sampling method. The participants in this study were 5 teenagers at SMP N 1 Gebog Kudus. Data collection techniques in this study were observation, interviews and documentation, with 14 open-ended questions. Data analysis techniques used in this study include: 1)Reading and Re-reading; 2)Initial Notes; 3)Developing Emergent Themes; 4)Searching for Connections a Cross Emergent Themes; 5)Moving the Next Cases; 6)Looking for Patterns Across Cases; and 7)Taking Interpretations to Deeper Levels. Research results: Based on the research analysis, there are 4 main themes, namely: (1)Dominant activities in spare time, (2)The emergence of emotional disturbances, (3)As entertainment when lonely, and (4)Being an important part of life. Conclusion: Smartphone is a very important communication tool for teenagers.